1994
DOI: 10.1161/01.atv.14.12.1933
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal insulin therapy corrects abnormalities in cholesteryl ester transfer and lipoprotein lipase activities in insulin-dependent diabetes mellitus.

Abstract: Patients with insulin-dependent diabetes mellitus (IDDM) have proatherogenic disturbances in cholesteryl ester transfer (GET) despite intensive subcutaneous insulin therapy (ISC). Since CET is activated by insulin-sensitive lipoprotein lipase (LPL), which normally increases postprandially, we queried whether iatrogenic hyperinsulinism from ISC stimulated LPL and CET by studying well-controlled IDDM patients after ISC and then 6 months after lowering systemic insulin levels by intraperitoneal (IP) insulin deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
48
2
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 53 publications
8
48
2
1
Order By: Relevance
“…In these patients, hepatic lipase activity has been demonstrated to be inversely correlated with the LDL triglycerides : cholesterol ratio [23,25]. The relative increase in the amount of LDL triglycerides could also be explained by the increased cholesteryl ester transfer protein activity demonstrated in these patients, especially if hepatic lipase activity is low [22,26]. This reasoning is consistent with the observed trend towards cholesteryl ester enrichment of VLDL in our study.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In these patients, hepatic lipase activity has been demonstrated to be inversely correlated with the LDL triglycerides : cholesterol ratio [23,25]. The relative increase in the amount of LDL triglycerides could also be explained by the increased cholesteryl ester transfer protein activity demonstrated in these patients, especially if hepatic lipase activity is low [22,26]. This reasoning is consistent with the observed trend towards cholesteryl ester enrichment of VLDL in our study.…”
Section: Discussionsupporting
confidence: 88%
“…Alternatively, a low VLDL triglycerides : apoB ratio could be attributable to increased lipoprotein lipase (LPL) activity. However, in several studies, type 1 diabetic patients and control subjects have been shown to have similar levels of LPL activity [22][23][24]. Moreover, if LPL activity were increased in type 1 diabetes mellitus, VLDL catabolism would be expected to be accelerated; however, this was not observed in the present study.…”
Section: Discussioncontrasting
confidence: 62%
“…Studies in humans which have examined the relative impact of subcutaneous compared to intraperitoneal insulin administration on lipid metabolism have generally [26,[63][64][65], although not always [24,66], found the intraperitoneal administration to be superior in normalising lipid metabolism. The characteristic dyslipidaemia of IDDM patients involves hypertriglyceridaemia and lowered HDL cholesterol concentrations [67].…”
Section: Discussionmentioning
confidence: 99%
“…However, the pancreatic hormone itself is inadequate in facilitating the activity of the CET. LPL helps activate the CET [22]. This underscores the importance of regular parenteral medication to augment the role of LPL and consequently CET especially in postprandial metabolism.…”
Section: Smoking On Lplmentioning
confidence: 87%